Recent Studies on the Maqāṣid al-Sharīʻah of Abū Isḥāq al-Shāṭibī:: A Systematic Literature Review - Kurniawan, Edi; Mustaniruddin, Ahmad; Rizani, Akhmad Kamil; Muchimah; Zaenuri, Ahmad; Muttaqin, Muhamad Zaenal (AJIS: Academic Journal of Islamic Studies, 2025)
This article examines the recent studies on al-Shāṭibī's maqāṣid al-sharīʻah (the highest purpose of Islamic Law) through a systematic literature review covering the years 2018-2023. Despite the growing interest in al-Shāṭibī's maqāṣid al-sharīʻah in contemporary discourse, research on this topic remains uncharted and unquantified. This article seeks to address the knowledge gap by examining the strengths and weaknesses of current studies and identifying potential areas for future research. This article employs a systematic literature review (SLR) as its research methodology, examining 20 scholarly articles selected from 139. This article concludes that scholars have studied al-Shāṭibī's maqāṣid al-sharīʻah across various fields, including Law, fiqh, health, language, comparative methodology, daʻwah, Sunnah, and logic. However, these studies rely heavily on literature review methods, with little to no empirical data. Thus, the key novelty of this article lies in uncovering a persistent theoretical bias in current research on maqāṣid, which limits its relevance to real-world legal and social challenges. This finding reveals an urgent need for more applied research that bridges al-Shāṭibī's normative theories with contemporary societal dynamics. This article underscores an opportunity for further research to build on al-Shāṭibī's maqāṣid al-sharīʻah theory through empirical data and to investigate new issues, including technology, education, banking, and Islamic finance.